Pancreatic Pseudocyst. Case Report and Literature Review - José Alberto Puerto Lorenzo; Lidia Torres Aja; Eslinda Cabanes Rojas (Revista Finlay)
Pancreatic pseudocyst is a local complication due to rupture of the pancreatic duct in acute or chronic pancreatitis, trauma or obstruction of the pancreatic duct. Its incidence is 1: 00,000 year and the prevalence is 6.0 % to 18.5 %. Acute forms usually resolve spontaneously in more than 40 % of cases and chronic forms usually do not disappear spontaneously and are at higher risk of complications. They can be drained by surgical, laparoscopic, percutaneous, and endoscopic methods. A case of a male patient who attended the surgery guard office due to abdominal pain in the epigastrium accompanied by abundant vomiting and a slight icteric tinge, it is presented. The case was studied and elective surgery was scheduled, opening of the anterior and posterior face of the stomach was performed. The Juracz surgical technique, a cystogastrostomy, was performed. The patient has been operated on for 1 year with a favorable evolution. Due to the rare nature of the case, its publication is decided.